Adaptasi dan Keberlanjutan Mata Pencaharian di Kampung Naga: Peran Pendidikan dalam Pengembangan Ekonomi Lokal - Dede Syaefudin; Sri Rahayu; Nia Sukmawati; Dodi Suhenda; Lina Herlina (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Kampung Naga, as a traditional community rich in customs, faces significant challenges from modernization. This study examines the relationship between education and the livelihoods of the indigenous people in Kampung Naga, Tasikmalaya, with a focus on adaptation and local economic sustainability. Kampung Naga, known for its cultural wealth and traditional customs, struggles to maintain its traditional livelihoods amid social and economic changes. The research employs qualitative methods, including interviews and direct observations, to explore how education can contribute to the economic empowerment of indigenous communities. The findings indicate that integrating traditional knowledge with formal education can enhance economic skills, strengthen economic resilience, and preserve local culture. Recommendations from this study include developing education curricula relevant to the needs of indigenous communities and increasing support from government and educational institutions to facilitate this adaptation process. This research aims to provide insights for policymakers and educators in designing programs that support the sustainability of indigenous livelihoods while preserving their cultural heritage.